2014
DOI: 10.1161/atvbaha.114.303086
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase Deficiency Exacerbates Angiotensin II–Induced Abdominal Aortic Aneurysms in Mice

Abstract: Objective— Although nicotinamide adenine dinucleotide phosphate oxidase 2 (NOX2) is reportedly essential for phagocyte host defenses, it has been found to aggravate atherosclerosis in apolipoprotein E ( Apoe )-null mice through excess production of superoxide. We therefore assessed the role of NOX2 in an experimental model of abdominal aortic aneurysm (AAA) and assessed the mechanism of NOX2 action in AAA. App… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 33 publications
(21 reference statements)
2
28
1
Order By: Relevance
“…Our findings are ostensibly in contrast with a recent experimental study in Nox2-deficient mice in which MMP-9 activity in the adventitia, but not media, was upregulated in aggravated abdominal aortic aneurysm (AAA) lesions, suggesting that a deficiency in Nox2 markedly perturbs proinflammatory cascades in macrophages present in AAA [43]. Thus, it is important to carefully monitor inflammatory phenotype when Nox2 intervention is conducted and this issue will also need to be investigated in humans.…”
Section: Discussioncontrasting
confidence: 79%
“…Our findings are ostensibly in contrast with a recent experimental study in Nox2-deficient mice in which MMP-9 activity in the adventitia, but not media, was upregulated in aggravated abdominal aortic aneurysm (AAA) lesions, suggesting that a deficiency in Nox2 markedly perturbs proinflammatory cascades in macrophages present in AAA [43]. Thus, it is important to carefully monitor inflammatory phenotype when Nox2 intervention is conducted and this issue will also need to be investigated in humans.…”
Section: Discussioncontrasting
confidence: 79%
“…demonstrated that p47phox was mainly expressed in macrophages and upregulated during cerebral aneurysm formation 26 . On the other hand, a recent study by Kigawa et al showed that NADPH oxidase deficiency can exacerbate angiotensin-II induced AAA formation in mice 27 . This unexpected occurrence of hyperinflammation by Nox2 deficiency is contrary to our findings where elastase-perfused Nox2 −/y mice were significantly protected from AAA.…”
Section: Discussionmentioning
confidence: 95%
“…The isolation of BMMs was performed as described in our previous study (33). Briefly, murine BM cells were collected by flushing femoral BM with culture medium; subsequently, the cells were incu- technology Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…BM transplantation. BM transplantation was conducted as previously described (33 were sacrificed, and aortic sinus and whole blood with EDTA were collected. Erythrocytes in the whole blood samples were lysed with BD Pharm Lyse (BD Biosciences); then the samples were analyzed by using BD FACSVerse (BD Biosciences) to evaluate the uptake of fluorescence beads in monocyte population.…”
Section: Methodsmentioning
confidence: 99%